India : Nutrition Determinants and Strategies in Nagaland - World Bank (World Bank, Washington, DC, 2019)
The state of Nagaland, with a population of two million, is situated in the North-East region of India. The state's topography is hilly with very poor roads and connectivity. The state has 11 districts, 52 blocks, and 1,500 villages. In 2014-15, per capita net state domestic product was estimated at US dollar 1,172 (INR 78,526), slightly lower than the national figure of US dollar 1,297 (INR 86,879). However, the socioeconomic distribution in Nagaland is more equitable than the national pattern, in 2012-13, an estimated 19 percent of the population lived below the official poverty line in the state, lower than the national average of 22 percent. Tribal communities make up almost 90 percent of Nagaland's population. The Nagaland Department of Health and Family Welfare (DoHFW) requested technical support for better understanding nutrition determinants and developing strategies that could be implemented at the community level with the support of the Nagaland Health Project. The objectives are to better understand the barriers to improved nutrition and health in Nagaland and to help the state government to develop strategies to address these issues. This involves analytical work (involving both primary and secondary data analysis) to identify gaps and bottlenecks, informing the development of contextually-appropriate and feasible strategies. Technical assistance focuses on supporting the state government in the design of strategies based on the findings of the analytical work. The development objectives of this advisory services and analytics (ASA) activity are: (i) to improve knowledge about the determinants of malnutrition in North East India; (ii) to identify gaps in maternal and child health and nutrition services for disadvantaged communities; and (iii) to support development of cross-sectoral strategies to combat malnutrition at the community level.